Predictive Factors of Lymph Node Metastasis in Early Mucinous Adenocarcinoma - Shangfeng LUAN (Cancer Biology & Medicine, 2009)
OBJECTIVE To identify clinicopathologic factors which predict lymph node metastases (LNM) in early mucinous adenocarcinoma patients, and to further explore the possibility of using minimally invasive treatment for patients with the disease.METHODS Data was collected from 38 patients with early mucinous adenocarcinoma who were surgically treated, and the association between clinicopathologic factors and the presence of LNM was retrospectively analyzed using univariate and multivariate logistic regression analysis.RESULTS Tumor size greater than 2.0 cm, the development of submucosal invasion, and the presence of lymphatic vessel involvement (LVI) were con fi rmed through univariate analysis as having a significant association with LNM and were considered to be significant and independent risk factors for LNM through multivariate analysis.CONCLUSION Tumor size > 2.0 cm, the development of submucosal invasion, and the presence of LVI are independent predictive factors for LNM in early mucinous adenocarcinoma. Minimally invasive treatment may be an effective treatment for intramucosal early mucinous adenocarcinoma when the tumor size is 2.0 cm or less, and if LVI has not occurred, as confi rmed by postoperative histologic examination.